A Detailed Insight into Nanostructured Lipid Carriers: A Versatile Drug Delivery System - Ghosh, Samarjit; Tiwari, Triveni; Nagaich, Upendra; Jain, Neha (Recent Patents on Nanotechnology, 2023)
The advent of technology provides a solution to various drug delivery-related problems by undertaking the development of a better drug delivery system, i.e., nano-sized drug delivery systems as they have shown huge prospects for effective delivery of drugs in the body. Nanostructured lipid carriers (NLCs) are such type of novel drug delivery system in which lipids of both solid and liquid types are used as a core for the disorganized matrix, which prevents the solid lipid crystallization and increases drug payload. They are generally composed of solid and liquid lipids, emulsifiers, drugs, and other various additives, which are selected based on purity, chemical stability, the concentration of materials required, compatibility, biodegradability, processing type, cost, and their regulatory status. Placing bioactives into nanostructured lipid carriers (NLCs) has enhanced pharmacokinetic characteristics by increasing therapeutic functionality and prolonging release from these carrier systems. In our opinion, the search involves two steps viz. fabrication strategies, production methods, and the impact of various types of substances on them, as well as the release mechanism and targeting modalities. In addition to other applications, the use of NLCs in gene therapy has marked a promising path for new and better drug delivery systems. Further development of various dosage forms using NLCs, like NLC based hydrogels, is being done for improving the overall aesthetic properties, leading to the desired therapeutic effect of the incorporated active. This review highlights several elements of NLCs, such as structural model and types, excipients utilized, factors affecting NLC production, preparation techniques, characterization, current applications, patents, challenges, and opportunities.
Keywords: nanotherapeutics